Alegría, tristeza lucharán para reconstruir su universo - alamo, Roberto; Vellés, Manuela 1987-; Casablanc, Pedro (Rakuten Cinema, 2018)
Marcos, Sandra and their daughter Lola form a vital and charismatic family. Marcos, a firefighter by profession and used to living in stressful situations, will receive a blow that will turn his life around. From then on, he will suffer a blockage that will not allow him to recognize the emotions of others or empathize with them. With the help of his family, and especially Lola, he will initiate a treatment to overcome this shock
Originally released as a motion picture in 2018
Extras: trailer, cast and crew credits, photo gallery, making-of featurette, music video clips
Keywords: Psychic trauma / Patients / Drama; Fathers and daughters / Drama; Families / Spain / Drama; Families; Fathers and daughters; Psychic trauma / Patients; Spain; Feature films; Fiction films; Drama; Film; DVD-Video